Histiocitose de células de Langerhans: rápida resolução após cessação do tabagismo Langerhans-cell histiocytosis: rapid resolution after smoking cessation - José Miguel Chatkin; Vinicius D. Silva; Carlos C. Fritscher; Jussara Fiterman; Cláudia Reck (Jornal Brasileiro de Pneumologia, 2005)
Descreve-se um caso de histiocitose pulmonar de células de Langerhans com relação estreita entre cessação do tabagismo e melhora radiológica. A tomografia computadorizada de alta resolução revelava múltiplos nódulos pequenos localizados em lobos superiores e campos médios de ambos os pulmões. O exame microscópico dessas lesões mostrava infiltração histiocitária, que se corava fortemente pela proteína S100. Apesar de a remissão espontânea poder ser uma possível explicação para essa evolução, este relato de caso mostra um rápido desaparecimento das lesões após o abandono do tabagismo. We describe a case of pulmonary Langerhans cell histiocytosis with a close temporal relationship between smoking cessation and radiological improvement. High-resolution computed tomography revealed multiple small nodules located in the upper and middle lobes of both lungs. Microscopy of these lesions showed histiocytic infiltration that reacted strongly to staining for S100 protein. The histiocytes resembling Langerhans cells showed strong reactivity for S100 protein. Smoking cessation was recommended and the patient complied. Chest X-ray and computed tomography performed 6 and 24 months later revealed almost complete resolution of the radiographic abnormalities. Despite the possibility that this evolution was attributable to spontaneous remission, in this case, the lesions did, in fact, disappear rapidly after smoking cessation.